2020
DOI: 10.1108/rpj-11-2019-0287
|View full text |Cite
|
Sign up to set email alerts
|

The effect of support structures on maraging steel MS1 parts fabricated by selective laser melting at different building angles

Abstract: Purpose This study aims to further the understanding of support structures and the likely impacts on maraging steel MS1 parts fabricated by selective laser melting (SLM) at 45°, 60° and 75° building angles. Design/methodology/approach Two groups of samples, one group with support structures and the other group without support structures, were designed with the same specifications and printed under the same conditions by SLM at 45°, 60° and 75° building angles. Differences in dimensional accuracy, surface rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Recently, Cao et al [27] studied the effect of support structures on the dimensional accuracy, hardness, and surface quality of SLM-built 18Ni-300 maraging steel at different build angles. The authors found the more accurate quality and higher microhardness for samples built with support structures than without.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Recently, Cao et al [27] studied the effect of support structures on the dimensional accuracy, hardness, and surface quality of SLM-built 18Ni-300 maraging steel at different build angles. The authors found the more accurate quality and higher microhardness for samples built with support structures than without.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…These defects have serious influences on the internal microstructure and mechanics of the final parts [49][50][51][52][53][54][55]. Therefore, after the parts being manufactured, post-processing operations are usually required to improve the mechanical properties and the surface quality, achieving their intended utilization [56][57][58][59][60][61][62]. There have many post-processing technologies, such as the thermal post-processing method to release thermally-induced residual stress and laser peening to reduce micro-defects and improve surface quality.…”
Section: Introductionmentioning
confidence: 99%
“…Leary et al (2018) shown that the mechanical properties, deformation and failure modes of Inconel 625 cellular lattice structures manufactured by SLM. Cao et al (2020) and Delcuse et al (2020) studied the effect of structures tilt angle on properties of the SLMed lattice part. Leary et al (2016) provided the manufacturability of lattice strut elements for a series of build inclinations and strut diameters.…”
Section: Introductionmentioning
confidence: 99%